QUANTITATIVE AND SEPARATE FLUENCE AND INTENSITY DEPENDENCES OF INFRARED MULTIPLE-PHOTON ABSORPTION IN SF6 - Hancock, G; Macrobert, A (1983)
Single-mode CO2-laser pulses, shaped by electro-optic crystal switching, have been used to measure multiple-photon absorption cross sections in SF6 as separate and quantitative functions of intensity and fluence at 944.2 cm-1. © 1983.